Analisis Penggunaan Model Ohlson Score (O-Score) Untuk Memprediksi Financial Distres Pada Perusahaan Tekstil Dan Garmen - Rahayu, Yuliastuti; Yahya; Idayati, Farida (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
The existence of the Policy for the Implementation of Restrictions on Community Activities (PPKM) has resulted in many people being forced to stay at home and even have to work at home so that the need for ready-made clothes and clothing materials is greatly reduced. The purpose of this study is to analyze the prediction of Financial Distress in textile and garment companies listed on the Indonesia Stock Exchange for the period 2018 – 2020 using the Ohlson O-Score model. This research is descriptive quantitative by calculating nine financial ratio indicators with a cut off of 0.038. If the results of the O-Score > cut off, the company is predicted to be in a state of distress (bankruptcy), but if the O-Score < cut off, the company is declared to be in a state of non-distress (healthy). From the results of the study, it can be concluded that during 2018 – 2019 eight textile and garment companies analyzed were in non-distress (healthy) conditions. During 2020 there are five companies that are predicted to be in distress (bankrupt), because these companies are unable to maintain their working capital, net income tends to decline and operating cash flow funds are in deficit, while the remaining three companies are still in a safe and healthy condition.